AN ALGORITHM FOR CALCULATING THE STEREO FACTOR - Costa, Thomaz Correa e Castro; Abreu, Natalia Carolina Oliveira (Floresta, 2024)
Information on wood volume is essential in forestry activities, especially in the sale of wood products. However, measuring solid volume during a harvest period is challenging. The viable parameter for measurement is stereo volume, which refers to the stacked quantity of wood, including the empty spaces between the logs. However, the stereo volume–cubic volume (solid) ratio, which is influenced by the taper, uniformity, and size of the trees, needs to be obtained. In most cases, if a field tester does not choose a reference value, the result is less than reliable. In this work, an algorithm is presented that estimates the stereo–cubic volume relationship from forest inventory and tree stacking data. It was implemented in Visual Basic for Applications (VBA) to simulate virtual log stacking. Its accuracy was evaluated in three field trials: the first and second in a eucalyptus stand and the third in a bamboo stand. Implementing the three calculation methods, the errors ranged from -12.34 to 8.33% for the cubing factor and from -8.94 to 15.64% for the stacking factor, which was the first degree of reliability for a parameter that requires a high level of accuracy because of the impact on wood buying and selling. The algorithm is easy to use but needs further validation in forest harvesting areas.